2005
DOI: 10.1128/jvi.79.14.9315-9319.2005
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Nonstructural Proteins NS1 and NS2 Mediate Inhibition of Stat2 Expression and Alpha/Beta Interferon Responsiveness

Abstract: Respiratory syncytial virus (RSV) subverts the antiviral interferon (IFN) response, but the mechanism for this evasion was unclear. Here we show that RSV preferentially inhibits IFN-␣/␤ signaling by expression of viral NS1 and NS2. Thus, RSV infection or expression of recombinant NS1 and NS2 in epithelial host cells causes a marked decrease in Stat2 levels and the consequent downstream IFN-␣/␤ response. Similarly, NS1/NS2-deficient RSV no longer decreases Stat2 levels or IFN responsiveness. RSV infection decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
264
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(271 citation statements)
references
References 25 publications
6
264
0
1
Order By: Relevance
“…With the sole exception of pneumoviruses, members of this family produce IFN-suppressor proteins such as V, W and C through co-transcriptional RNA editing of the viral P gene [10,[13][14][15]. Pneumoviruses, represented by RSV, do not use RNA editing; instead, they uniquely encode two nonstructural (NS) proteins, NS1 and NS2, which strongly suppress both IFN induction and IFNresponse pathways by inhibiting or degrading a number of signaling proteins involved in these two pathways [16][17][18][19][20][21][22][23][24][25][26][27][28][29], and thus act as essential virulence factors [30][31][32]. In pursuing the mechanism by which the NS proteins target such a diverse array of immune proteins that share little or no sequence identity, we wondered whether there is a common location of NS proteins and their targets.…”
Section: Introductionmentioning
confidence: 99%
“…With the sole exception of pneumoviruses, members of this family produce IFN-suppressor proteins such as V, W and C through co-transcriptional RNA editing of the viral P gene [10,[13][14][15]. Pneumoviruses, represented by RSV, do not use RNA editing; instead, they uniquely encode two nonstructural (NS) proteins, NS1 and NS2, which strongly suppress both IFN induction and IFNresponse pathways by inhibiting or degrading a number of signaling proteins involved in these two pathways [16][17][18][19][20][21][22][23][24][25][26][27][28][29], and thus act as essential virulence factors [30][31][32]. In pursuing the mechanism by which the NS proteins target such a diverse array of immune proteins that share little or no sequence identity, we wondered whether there is a common location of NS proteins and their targets.…”
Section: Introductionmentioning
confidence: 99%
“…RSV non-structural proteins have been shown to interact with several host nuclear, cytosolic and mitochondrial factors, leading to suppression of the antiviral response, cell cycle regulation, DNA damage repair and culminating in G 0 /G 1 phase cell cycle arrest (Atreya et al, 1998;Bossert et al, 2003;Boyapalle et al, 2012;Elliott et al, 2007;Lo et al, 2005;Munday et al, 2010;Munir et al, 2011;Ren et al, 2011;Schlender et al, 2000;Spann et al, 2004Spann et al, , 2005Wu et al, 2012;Xu et al, 2014). TGF-b expression during RSV infection has been shown to be important for cell cycle inhibition in the G 0 /G 1 phase (Gibbs et al, 2009;McCann & Imani, 2007;Wu et al, 2011) and miR-24 has been shown to be suppressed by TGF-b (Sun et al, 2008), as well as regulate TGF-b precursor processing (Luna et al, 2011).…”
Section: Rsv Ns1 Modulates Tgf-b Expression Via Klf6mentioning
confidence: 99%
“…Codon deoptimized RSV is attenuated in vitro, but evokes a strong humoral response upon vaccination and challenge (Meng et al, 2014). These and other immune modulators inhibit the development of the antiviral state (Bossert et al, 2003;Elliott et al, 2007;Goswami et al, 2013;Lo et al, 2005;Moore et al, 2008;Oshansky et al, 2009a;Spann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations